Effect of Storage Conditions on Physicochemical Characteristics and Phenolic Compounds of Eggplant (Solanum melongena L.) - Barragán-López, José Andrés; Franco-Peñata, Arlet Patricia; López-Pastén, Jessica; Pérez-Cervera, Carmen Elena (Revista de Ciencias Agrícolas, 2019)
High demand for fresh fruit and vegetables requires the implementation of techniques to extend the shelf life of these highly perishable products. A widely used method for this purpose is the refrigeration; however, it is known that most of the vegetables preserved in this way evidence chilling injury signs during storage. Eggplants cv C029 recently harvested were stored at 13°C packed into low-density polyethylene bags either with perforations (PPB), vacuum packaged (VPB), or unpacked during 5, 10, 15 and 20 days to evaluate the effect of chilling on physicochemical characteristics and visual appearance. Unpacked Eggplants presented remarkable chilling injury symptoms, losing its commercial quality before 10d of storage. Fruit stored in VPB showed discoloration affecting visual appearance but maintains the phenolic compounds and avoided pulp and seeds browning. Eggplants packed in PPB showed the best results in this work, preserving overall characteristics during 15d.